Epidemiological panel of pregnant patients undergoing appendectomy at a reference center in the Amazon from january 2015 to october 2021 (Research, Society and Development, 2024)
Objective: To describe an epidemiological panel of pregnant women surgically approached due to acute appendicitis in a reference hospital in the Amazon between January 2015 and October 2021. Methodology: An observational, retrospective and descriptive study was carried out, using data from medical records of pregnant patients who underwent appendicectomies at the FSCMPA during the proposed period. Data analysis: It was performed using the BioEstat 5.0 program, the G test was used to compare categories and the significance value for analysis was less than 5% (5% alpha). Result: A study with 30 pregnant women who underwent appendectomy in Belém-Pará between March 2015 and October 2021 revealed that the majority were between 21 and 30 years old and were in the 2nd trimester of pregnancy. About 46.7% had a positive histological diagnosis for appendicitis, with ultrasonography being the most requested test (56.7%). The average length of stay was 10 days, with no significant association with exams or histological diagnosis, but there was a relationship with gestational age. The request for imaging tests was associated with the presence of fever. Final considerations: The study analyzed appendicitis in pregnant women in the Amazon, with similar results to other studies. He highlighted complications in the third trimester, correlation between fever and imaging tests, and low rate of misdiagnosis. In addition, it pointed out problems in the records of local hospitals.